Long-Term Survival and Intracellular Replication of Mycoplasma hominis in Trichomonas vaginalis Cells: Potential Role of the Protozoon in Transmitting Bacterial Infection - Dessì, Daniele (American Society for Microbiology, 2005)
The existence of a symbiotic relationship between Trichomonas vaginalis and Mycoplasma hominis, which is the first reported example of symbiosis between two obligate human pathogens, has been recently reported by our research group. In this work, we examined the cellular location of M. hominis in respect to T. vaginalis. By using gentamicin protection assays, double immunofluorescence, and confocal microscopy, we obtained strong evidence that M. hominis is located within protozoan cells. 5-Bromodeoxyuridine incorporation assays showed that intracellularly located mycoplasmas actively synthesize DNA. Our results demonstrate that M. hominis has the capability of entering trichomonad cells and of replicating inside the protozoon. These findings suggest that symbiosis might provide the bacteria, during human infection, with the capability to resist to environmental stresses, such as host defense mechanisms and pharmacological therapies.